2013
DOI: 10.1371/journal.pone.0054476
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tick-Borne Pathogens in Ixodes ricinus and Dermacentor reticulatus Ticks from Different Geographical Locations in Belarus

Abstract: Worldwide, ticks are important vectors of human and animal pathogens. Besides Lyme Borreliosis, a variety of other bacterial and protozoal tick-borne infections are of medical interest in Europe. In this study, 553 questing and feeding Ixodes ricinus (n = 327) and Dermacentor reticulatus ticks (n = 226) were analysed by PCR for Borrelia, Rickettsia, Anaplasma, Coxiella, Francisella and Babesia species. Overall, the pathogen prevalence in ticks was 30.6% for I. ricinus and 45.6% for D. reticulatus. The majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
81
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 41 publications
20
81
1
8
Order By: Relevance
“…and Babesia spp., and with A. phagocytophilum and Babesia spp. Such co-infections were also not detected by other authors who examined D. reticulatus for the presence of a greater number of pathogens in Belarus [27], Serbia [28], Russia [20], and Poland [59], while in most studies on I. ricinus complex, these co-infections are usually reported and analyzed. Thus, Belongia [2] and Swanson et al [1] report in their review articles the prevalence of dual co-infections between B. burgdorferi s. l. and A. phagocytophilum or Babesia microti/B.…”
Section: Toxoplasma Gondiimentioning
confidence: 78%
See 3 more Smart Citations
“…and Babesia spp., and with A. phagocytophilum and Babesia spp. Such co-infections were also not detected by other authors who examined D. reticulatus for the presence of a greater number of pathogens in Belarus [27], Serbia [28], Russia [20], and Poland [59], while in most studies on I. ricinus complex, these co-infections are usually reported and analyzed. Thus, Belongia [2] and Swanson et al [1] report in their review articles the prevalence of dual co-infections between B. burgdorferi s. l. and A. phagocytophilum or Babesia microti/B.…”
Section: Toxoplasma Gondiimentioning
confidence: 78%
“…The latter association showed a significantly higher prevalence rate than expected. Reye et al [27] found coinfections in 3 out 226 D. reticulatus ticks (1.3%) which were collected in Belarus and tested for the presence of 7 pathogens. This value, which is 6.5 times lower compared to the current study, concerned in all cases co-infections between B. burgdorferi s.l.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dermacentor reticulatus Fabricius 1794 is the three-host meadow tick that parasitizes primarily wild and domestic mammals and, infrequently, humans. Recent comparative analyses have revealed changes in the distribution and abundance (almost doubled) of D. reticulatus ticks in some European countries, implying a higher risk of the transmission of tick-borne diseases [15][16][17]. The development of molecular diagnostic tools has not only enhanced opportunities for collecting important…”
Section: Introductionmentioning
confidence: 99%